The Role of Mother Tongue in Indonesian Language Learning: Influences, Challenges and Implications - Ndraha, Laurensia; Bawamenewi, Arozatulo; Harefa, Esther Novi Christin; Halawa, Alexander Julvin (Journal Emerging Technologies in Education, 2024)
Background. This research is a continuation of previous studies conducted by other researchers. The reason for this is because many students tend to rely on their mother tongue while in class or in the learning process. This reliance greatly affects children's listening skills. Purpose The researcher's aim was to investigate the impact of mother tongue use on students' language skills, especially in Nias Islands, with a focus on communication during the teaching and learning process.   Method. This research used a descriptive approach within a qualitative methodological framework. The research used assessment tools to evaluate language selection, semantic appropriateness, and the use of affixes. The data was collected through classroom observations and interviews with Indonesian language teachers in related schools. Results. The results show that many students still use their mother tongue when communicating with teachers, although some have shown partial proficiency in Indonesian, but still mix it with mother tongue. Conclusion Observation was the method that influenced the findings of this study, as it allowed the researcher to directly observe the students' use of language during the learning process.